Математика в поліцейській діяльності: основи, особливості, математична підготовка - Сербенюк, С. О.; Serbenyuk, S. O. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 4 (103). - С. 333-344, 2023)
Наукове дослідження присвячено введенню навчальної дисципліни «Математичні методи в поліцейській діяльності» та обговоренню змісту її першого модуля для здобувачів освіти закладів вищої освіти Міністерства внутрішніх справ України з метою поєднання математичних методів, а також елементів фізики, астрономії та географії для вирішення практичних завдань у професійній діяльності поліцейських. Сформульовано деякі складові першого модуля цієї дисципліни на основі онлайн-курсу з вивчення математики пожежниками-рятувальниками у США.

The main attention is paid to the introduction of a comprehensive academic discipline “Mathematical Methods in Police Activity” for the first time and the discussion of the content of its first module for students of higher education institutions subordinated to the Ministry of Internal Affairs of Ukraine with the aim of combining mathematical methods, as well as elements of physics, astronomy and geography, in particular topography, to solve practical problems in the professional activity of police officers. Some components of the first module of this discipline are formulated on the basis of a study of an online course on mathematics for firefighters and rescuers in the United States. The problem of introducing a course in mathematics or elements of applied mathematics (mathematics and methods of solving tasks for professional purposes) or applied mathematics with elements of natural science (an integrated course in astronomy, physics and geography) into the educational process of training future police officers has not been studied in a comprehensive manner. There are some recommendations on the expediency of studying statistics, but there are many branches of mathematics whose methodology is useful for solving applied problems in the fields of justice and law enforcement. The need for such a study is due to the lack of a universal course for police officers in the world practice that would combine practical problem solving, mathematical methods, physical laws and processes, astronomy and geography, including topography. The formulated components of the first module of the course are relatively complete in terms of content and form the knowledge necessary to develop the skills and abilities to perform elementary calculation professional tasks and to comply with and understand safety rules. The article is the first in a series of articles on the relevant topic, some of which are in the process of preparation or are preprints.

Научное исследование посвящено введению учебной дисциплины «Математические методы в полицейской деятельности» и обсуждению содержания его первого модуля для соискателей высшего образования Министерства внутренних дел Украины с целью сочетания математических методов, а также элементов физики, астрономии и географии для решения практических задач в профессиональной деятельности полицейских. Сформулированы некоторые составляющие первого модуля этой дисциплины на основе онлайн-курса по изучению математики пожарными-спасателями в США.
Mathematics in police activity: basics, features, mathematical training
Keywords: математичні методи; статистика; підготовка поліцейських; закони фізики; астрономія; топографія; зарубіжний досвід; mathematical methods; statistics; police training; laws of physics; astronomy; topography; foreign experience; математические методы; подготовка полицейских; законы физики; астрономия; топография; зарубежный опыт